Suna Çağaptay, The First Capital of the Ottoman Empire. The Reli¬gious, Architectural and Social History of Bursa - VOJADJIS (Σωτήρης ΒΟΓΙΑΤΖΗΣ) Sotiris (Δελτίον της Χριστιανικής Αρχαιολογικής Εταιρείας, 2023)
Suna Çağaptay, The First Capital of the Ottoman Empire. The Religious, Architectural and Social History of Bursa, I. B. Tauris, London 2021, 214 pp., 16×23 cm., 20 figs, bibliography, index, ISBN: HB: 978-1-8386-0549-0.